1997
DOI: 10.1016/s0735-1097(96)00439-1
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Chamber and Appendage Function After Internal Atrial Defibrillation: A Prospective and Serial Transesophageal Echocardiographic Study

Abstract: Internal atrial defibrillation causes depressed left atrial chamber and appendage function and may result in the subacute accumulation of spontaneous echo contrast and development of new thrombi after cardioversion. These findings have important clinical implications for anticoagulation therapy before and after low energy internal atrial defibrillation in patients with atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(42 citation statements)
references
References 18 publications
4
34
1
3
Order By: Relevance
“…Top, patient with CBE;Bottom, control subject; Right, maximumLAAarea; Left, minimumLAAarea (transverse plane by transesophageal echocardiograms). It has been clearly shown that left atrial dysfunction due to atrial stunning can be recovered for dozens of minutes after the cessation of PAF, whereas, prolongation of the atrial stunning has been suggested to play a critical role in the thrombus formation in LAA by experimental studies (39)(40)(41)(42) Previous clinical reports demonstrate that the nature of altered coagulation and fibrinolysis are different in various subtypes of ischemic stroke (45). Especially, plasma levels of D-dimer and thrombin-antithrombin III complex are significantly higher in cases with cardioembolic stroke, compared with atherothrombotic or lacunar stroke (46).…”
Section: Resultsmentioning
confidence: 99%
“…Top, patient with CBE;Bottom, control subject; Right, maximumLAAarea; Left, minimumLAAarea (transverse plane by transesophageal echocardiograms). It has been clearly shown that left atrial dysfunction due to atrial stunning can be recovered for dozens of minutes after the cessation of PAF, whereas, prolongation of the atrial stunning has been suggested to play a critical role in the thrombus formation in LAA by experimental studies (39)(40)(41)(42) Previous clinical reports demonstrate that the nature of altered coagulation and fibrinolysis are different in various subtypes of ischemic stroke (45). Especially, plasma levels of D-dimer and thrombin-antithrombin III complex are significantly higher in cases with cardioembolic stroke, compared with atherothrombotic or lacunar stroke (46).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism seems to be a 'stunning' of the left atrial appendage in cardioversion first reported during direct current conversion where patients developed a new spontaneous echo contrast and impaired velocities in the left atrial appendage, which could predispose to thrombus formation [12,34] . One embolic event has been described in a patient with a therapeutic anticoagulation level without thrombus formation but with a low velocity flow in the left atrial appendage and spontaneous echo contrast, after internal cardioversion with a lower energy than that needed for direct currentcardioversion [35] . A proposed mechanism has been administration of electrical energy.…”
Section: Thrombi and Velocities In The Left Atrial Appendagementioning
confidence: 99%
“…It is known that LAA contractile dysfunction present immediately after cessation of AF by successful cardioversion recovers gradually to levels approximately equivalent to that in control groups within 1 week [11,12,13]. Few prior studies measured LAA flow after long-term maintenance of sinus rhythm.…”
Section: Discussionmentioning
confidence: 99%